2020
DOI: 10.3390/f11060706
|View full text |Cite
|
Sign up to set email alerts
|

Co-Creating Conceptual and Working Frameworks for Implementing Forest and Landscape Restoration Based on Core Principles

Abstract: Existing guidelines and best-practices documents do not satisfy, at present, the need for guiding implementation of Forest and Landscape Restoration (FLR) based on core principles. Given the wide range of FLR practices and the varied spectrum of actors involved, a single working framework is unlikely to be effective, but tailored working frameworks can be co-created based on a common conceptual framework (i.e., a common core set of principles and a generalized set of criteria and indicators). We present backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 55 publications
0
55
0
3
Order By: Relevance
“…Increasingly, tree plantings have been established to provide ecosystem services (Lamb, 2018) and have employed mixed‐species plantations and agroforestry (Liu et al., 2018). Many recent tree planting efforts are part of national commitments to forest and landscape restoration , which combine protective and productive reforestation schemes for increasing tree cover across heterogeneous, multipurpose landscapes (Table 2; Chazdon, Gutierrez, Brancalion, Laestadius, & Guariguata, 2020).…”
Section: People Plant Trees For Many Different Reasonsmentioning
confidence: 99%
“…Increasingly, tree plantings have been established to provide ecosystem services (Lamb, 2018) and have employed mixed‐species plantations and agroforestry (Liu et al., 2018). Many recent tree planting efforts are part of national commitments to forest and landscape restoration , which combine protective and productive reforestation schemes for increasing tree cover across heterogeneous, multipurpose landscapes (Table 2; Chazdon, Gutierrez, Brancalion, Laestadius, & Guariguata, 2020).…”
Section: People Plant Trees For Many Different Reasonsmentioning
confidence: 99%
“…Thus, a recent review of FLR practice concluded that "Existing guidelines and best practices documents do not satisfy, at present, the need for guiding the implementation of Forest and Landscape Restoration (FLR) based on core principles. Given the wide range of FLR practices and the varied spectrum of actors involved, a single working framework is unlikely to be effective, but tailored working frameworks can be co-created based on a common conceptual framework" [47]. While FLR is supposed to support sustainable agricultural production, there is very little discussion on how this can be achieved.…”
Section: Beyond Tree Planting the Various Aspects Of Restorationmentioning
confidence: 99%
“…The diversity of outcomes and magnitude of restoration expected under global targets require processes that go beyond business-as-usual [24]. However, despite its promise, the effectiveness of landscape approaches has not been adequately demonstrated [25], and there is a limited amount of evidence on FLR outcomes and impacts [26]. Chazdon et al [26], in this issue, provide a critical overview of the need for tailored working frameworks based on a common conceptual framework founded in a core set of principles.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its promise, the effectiveness of landscape approaches has not been adequately demonstrated [25], and there is a limited amount of evidence on FLR outcomes and impacts [26]. Chazdon et al [26], in this issue, provide a critical overview of the need for tailored working frameworks based on a common conceptual framework founded in a core set of principles. The six principles for FLR revised by the Global Partnership on Forest and Landscape Restoration (GPFLR) [16] are largely accepted by researchers and practitioners.…”
Section: Introductionmentioning
confidence: 99%